Simple and extended reproduction of fixed assets: a retrospective and current trends - N. L. Antonova; L. A. Antonov (Путеводитель предпринимателя)
The article deals with the reproduction of fixed assets. The definitions of the notion «Reproduction» of various authors are given and their analysis is carried out. Describes a simple and advanced method of reproduction, with an emphasis on the independence of the nature of the reproduction of fixed assets from the method ofdepreciation. A retrospective analysis of the development of the theory and practice of reproduction and amortization is carried out.